Comparison of a Shastry-Sutherland lattice stability in Ce2Pd2Sn as a function of field and doping - Sereni, J.G. (2011)
Fil: Sereni, J. G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina